2016
DOI: 10.1177/1078087416651935
|View full text |Cite
|
Sign up to set email alerts
|

Incented Voluntary Municipal Mergers as a Two-Stage Process: Evidence from the Swiss Canton of Fribourg

Abstract: Voluntary mergers of local jurisdictions in Europe gained in importance in the last two decades. A debated but rarely analyzed issue in this field is the impact of different local characteristics on the probability to merge. The paper contributes to this debate by assessing the importance of local determinants in two stages of a merger process. The quantitative study of a large-scale territorial reform in the Swiss canton of Fribourg shows that factors linked to the functional dimension of local government, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
(83 reference statements)
2
10
0
Order By: Relevance
“…Moreover, municipalities with strong right-wing parties and municipalities that would lose political influence as a result of a merger are more likely to vote against a merger project. These findings are in line with existing research on local government amalgamation -potential scale economy benefits have been found to matter for decisions in Japanese (Miyazaki 2014) and Swiss (Strebel 2018) local merger referenda. In addition, concerns for political control are associated with municipal mergers in a variety of different contexts (Marando and Whitley 1972;Hyytinen, Saarimaa, and Tukiainen 2014;Jakobsen and Kjaer 2016;Strebel 2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, municipalities with strong right-wing parties and municipalities that would lose political influence as a result of a merger are more likely to vote against a merger project. These findings are in line with existing research on local government amalgamation -potential scale economy benefits have been found to matter for decisions in Japanese (Miyazaki 2014) and Swiss (Strebel 2018) local merger referenda. In addition, concerns for political control are associated with municipal mergers in a variety of different contexts (Marando and Whitley 1972;Hyytinen, Saarimaa, and Tukiainen 2014;Jakobsen and Kjaer 2016;Strebel 2018).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with existing research on local government amalgamation -potential scale economy benefits have been found to matter for decisions in Japanese (Miyazaki 2014) and Swiss (Strebel 2018) local merger referenda. In addition, concerns for political control are associated with municipal mergers in a variety of different contexts (Marando and Whitley 1972;Hyytinen, Saarimaa, and Tukiainen 2014;Jakobsen and Kjaer 2016;Strebel 2018). This in turn suggests that the findings of this study might be generalizable to other contexts in which local referenda on municipal mergers are held, such as Finland, Japan and the US.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations